NT-proBNP during and after primary PCI for improved scheduling of early hospital discharge - Schellings, Dirk; Giannitsis, Evangelos (Netherlands heart journal, 2017)
The Zwolle Risk Score (ZRS) identifies primary percutaneous coronary intervention (PPCI) patients at low mortality risk, eligible for early discharge. Recently, this score was improved by adding baseline NT-proBNP. However, the optimal timepoint for NT-proBNP measurement is unknown. PPCI patients in the On-Time 2 study were candidates. The ZRS and NT-proBNP levels on admission, at 18–24 h, at 72–96 h, and the change in NT-proBNP from baseline to 18–24 h (delta NT-proBNP) were determined. We investigated whether addition of the different NT-proBNP measurements to the ZRS improves the prediction of 30-day mortality. Based on cut-off values reflecting zero mortality at 30 d, patients who potentially could be discharged early were identified and occurrence of major adverse cardiac events (MACE) and major bleeding until 10 d was registered. 845 patients were included. On multivariate analyses, NT-proBNP at baseline (HR 2.09, 95% CI 1.59–2.74, p < 0.001), at 18–24 h (HR 6.83, 95% CI 2.94–15.84), and at 72–96 h (HR 3.32, 95% CI 1.22–9.06) independently predicted death at 30 d. Addition of NT-proBNP to the ZRS improved prediction of mortality, particularly at 18–24 h (net reclassification index 29%, p < 0.0001, integrated discrimination improvement 17%, p < 0.0001). Based on ZRS (<2) or NT-proBNP at 18–24 h (<2500 pg/ml) 75% of patients could be targeted for early discharge at 48 h, with expected re-admission rates of 1.2% due to MACE and/or major bleeding. NT-proBNP at different timepoints improves prognostication of the ZRS. Particularly at 18–24 h post PPCI, the largest group of patients that potentially could be discharged early was identified.
Published online: 9 December 2016
Gesehen am 20.04.2018